Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/molecules26061635
|View full text |Cite
|
Sign up to set email alerts
|

Kushenol C Prevents Tert-Butyl Hydroperoxide and Acetaminophen-Induced Liver Injury

Abstract: Sophora flavescens, also known as Kushen, has traditionally been used as a herbal medicine. In the present study we evaluated the ameliorative effects of kushenol C (KC) from S. flavescens against tBHP (tert-Butyl hydroperoxide)-induced oxidative stress in hepatocellular carcinoma (HEPG2) cells and acetaminophen (APAP)-induced hepatotoxicity in mice. KC pretreatment protected the HEPG2 cells against oxidative stress by reducing cell death, apoptosis and reactive oxygen species (ROS) generation. KC pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Given the central role of mitochondrial dysfunction in APAP-induced cell death, it is critical to specifically assess mitochondrial function. Unfortunately, most studies neglect to evaluate the above-mentioned, well-defined pathways of the APAP pathophysiology and generally omit analysis of mitochondrial function when using the model 93 , 94 . The mere focus on measurement of BAX protein levels rather than its mitochondrial translocation, which is the pathophysiological relevant feature, is another common issue 93 , 95 .…”
Section: General Recommendations For Investigating Therapeutic Efficacy and Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the central role of mitochondrial dysfunction in APAP-induced cell death, it is critical to specifically assess mitochondrial function. Unfortunately, most studies neglect to evaluate the above-mentioned, well-defined pathways of the APAP pathophysiology and generally omit analysis of mitochondrial function when using the model 93 , 94 . The mere focus on measurement of BAX protein levels rather than its mitochondrial translocation, which is the pathophysiological relevant feature, is another common issue 93 , 95 .…”
Section: General Recommendations For Investigating Therapeutic Efficacy and Mechanisms Of Actionmentioning
confidence: 99%
“…Unfortunately, most studies neglect to evaluate the above-mentioned, well-defined pathways of the APAP pathophysiology and generally omit analysis of mitochondrial function when using the model 93 , 94 . The mere focus on measurement of BAX protein levels rather than its mitochondrial translocation, which is the pathophysiological relevant feature, is another common issue 93 , 95 . Even studies which purport to evaluate JNK activation merely examine changes in the whole liver rather than a more relevant examination of its mitochondrial translocation 95 .…”
Section: General Recommendations For Investigating Therapeutic Efficacy and Mechanisms Of Actionmentioning
confidence: 99%
“…When L-02 cells were treated with 400 µmol/L of TBHP for 4 h, the L-02 cell injury model was successfully established. The results showed that anserine could effectively alleviate L-02 cell injury induced by TBHP, and no significant proliferative effects or toxic side effects were found for treatment with 5–80 mmol/L of anserine in L-02 cells within 12 h. Similarly, Cho BO, et al successfully established a model of TBHP-induced liver injury in HepG2 cells to evaluate the liver injury repair function of kushenol C [ 28 ]. Rutin has also been proven to attenuate oxidative damage induced by TBHP in HepG2 cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hussein and colleagues found that chlorogenic acid, quercetin, coenzyme Q10, and silymarin reduced hepatic cell death and decreased ROS production [46]. Furthermore, another scientific research reported that Kushenol C reduced cell death by downregulating ROS levels and upregulating antioxidant enzyme expression, giving a more direct evidence that less oxidative stress induced less cell death [47]. Irisin exhibited antioxidant effects by improving abnormal cell death.…”
Section: Irisin Decreases Er Stressmentioning
confidence: 99%